Observer-based deadbeat predictive speed controller for surface-mounted PM synchronous motor. (April 2021) - Nguyen, Anh Tuan; Rafaq, Muhammad Saad; Choi, Han Ho; Jung, Jin-Woo
Abstract: This paper investigates an observer-based deadbeat predictive speed controller (DBPSC) for a prototype surface-mounted permanent magnet synchronous motor (SPMSM) drive system. Unlike the conventional deadbeat controllers which are mainly used for deadbeat current control in the inner loop in a cascaded control structure, the proposed deadbeat controller is designed by incorporating a speed controller with a load torque disturbance observer. Specifically the proposed deadbeat speed control law consists of a deadbeat stabilizing feedback control term and a compensation control term. The stability of the proposed closed-loop system is assured based on the former term by forcing all poles of the dynamic error vector toward the origin within a short transient time, which guarantees a fast transient response of the control system by using the solution of an optimal control problem. The latter term is proposed based on the predicted q -axis current to compensate for the model nonlinearities and parameter uncertainties. Next, the deadbeat load torque observer (DBLTO) is proposed to provide a precisely estimated load torque with a high estimation rate for the predicted q -axis current in the latter term, which helps the proposed scheme in obtaining a small steady-state error (SSE), a low total harmonic distortion (THD), and robustness against the parameter variations. In addition, the proposed scheme possesses a simple structure, so it reduces the computational burden for digital implementation. The Lyapunov theory is utilized in the stability proof process of the proposed observer-based method. Finally, the comparative studies between the proposed DBPSC and a conventional deadbeat speed controller (DBSC) are performed under the sudden changes of speed and load torque through simulations on MATLAB/Simulink and experiments on a prototype SPMSM drive using a TI TMS320F28335 DSP platform. Graphical abstract: Highlights: An observer-based deadbeat predictive speed controller for SPMSM is proposed. All poles of the dynamic error vector are forced toward the origin in a short time. Parameter uncertainties are compensated based on the predicted q -axis current. The improved robustness is proven via the root locus in z -plane. The load torque is precisely estimated via the deadbeat load torque observer.